The First Implementation of Music at High Schools in Vietnam - Anh, Ta Hoang Mai (European Journal of Applied Sciences, 2022)
After several educational reforms, in the 2018 general education program, music has officially implemented in high school level as an elective subject with the content and requirements to be consistent with other grades. This process goes through several periods such as compilation and assessment of new textbooks; training teachers to implement the program to meet the differentiation and career orientation of students.